2017
DOI: 10.2147/copd.s128358
|View full text |Cite
|
Sign up to set email alerts
|

Risk of pneumonia with budesonide-containing treatments in COPD: an individual patient-level pooled analysis of interventional studies

Abstract: BackgroundConcerns have been raised that treatment of COPD with inhaled corticosteroids may increase pneumonia risk. Responding to a request from the European Medicines Agency Pharmacovigilance Risk Assessment Committee, a pooled analysis of interventional studies compared pneumonia risk with inhaled budesonide-containing versus non-budesonide-containing treatments and the impact of other clinically relevant factors.MethodsAstraZeneca-sponsored, parallel-group, double-blind, randomized controlled trials meetin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…A metaanalysis of 7 studies with >7000 patients found no increase in pneumonia rates following budesonide treatment with or without a LABA component in patients with COPD [20]. A recently updated pooled analyses of 11 studies with >10,000 patients also found no statistically significant increase in overall risk of pneumonia treatment-emergent AEs following budesonide treatment (with or without a LABA) in patients with COPD versus non-budesonide comparators (formoterol or placebo) [21]. Our findings suggest that the ICS component of budesonide/formoterol pMDI 320/9 mg combination treatment provides clinical benefit for patients with COPD without an apparent causal relationship for the development of pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…A metaanalysis of 7 studies with >7000 patients found no increase in pneumonia rates following budesonide treatment with or without a LABA component in patients with COPD [20]. A recently updated pooled analyses of 11 studies with >10,000 patients also found no statistically significant increase in overall risk of pneumonia treatment-emergent AEs following budesonide treatment (with or without a LABA) in patients with COPD versus non-budesonide comparators (formoterol or placebo) [21]. Our findings suggest that the ICS component of budesonide/formoterol pMDI 320/9 mg combination treatment provides clinical benefit for patients with COPD without an apparent causal relationship for the development of pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“… 84 89 , 102 In addition, potential differences in risk for pneumonia may be affected by the specific ICS used. 86 , 103 , 104 Therefore, considering a patient’s prior history of pneumonia may be important when choosing ICS therapy as part of the COPD-treatment regimen.…”
Section: Ics-treatment Considerations In Copdmentioning
confidence: 99%
“… 3 7 On the other hand, most double-blind, randomized controlled studies with budesonide treatment alone or in combination with the LABA formoterol reported no increased risk of pneumonia when compared with formoterol alone or placebo. 8 Furthermore, large observational, population-based studies in real-world, clinical practice with COPD patients have suggested a higher risk of pneumonia for therapy with FP than with budesonide. 9 12 Similarly, a recent evaluation of meta-analyses that considered the risk of pneumonia related to treatment of COPD patients with FP or budesonide showed an association with FP causing a statistically significant increased risk of pneumonia, whereas budesonide showed no association.…”
Section: Introductionmentioning
confidence: 99%